Port of L.A. - Herbert Muschamp (Oz, 1991)
The architect was Franklin D. Israel Design Associates, while the text/critique was written by Herbert Muschamp. When Frank Israel was a child in New York, you could drive along the West Side Highway on any weekend and pass seven or eight luxury liners tied up at the Hudson piers. Of course, jet travel had already made the liners obsolete by then, but nobody wanted to tell them that, because these ships were among the most beautiful, heart-lifting sights to behold in New York.